Avaliação dos níveis de resposta das emissões otoacústicas em neonatos com asfixia perinatal - Ribeiro, Georgea Espindola [UNESP]; Silva, Daniela Polo Camargo da [UNESP]; Montovani, Jair Cortez [UNESP] (Sociedade de Pediatria de São Paulo, 2014)
Objective: To evaluate the effects of perinatal asphyxia on the level of the response to transient otoacoustic emissions in infants.Methods: Otoacoustic emissions in 154 neonates were performed: 54 infants who suffered asphyxia at birth, measured by Apgar score and medical diagnosis, and 100 infants without risk were compared. Scores less than 4 in the first minute and/or less than 6 in the fifth minute were considered as low Apgar. Statistical analysis of the data was performed using the Kruskal, Wilcoxon, and Mann-Whitney nonparametric tests.Results: Lower levels of response were observed in transient otoacoustic emission in the group that suffered perinatal asphyxia, with significant values for the frequencies 2,000, 3,000, and 4,000 Hz in the right ear, and 2,000 and 4,000 Hz in the left ear.Conclusions: The analysis of the intrinsic characteristics of the otoacoustic emissions evidenced low performance of outer hair cells in neonates who had perinatal asphyxia, which may affect the development of listening skills in this population.

Objetivo Avaliar os efeitos da asfixia perinatal sobre os níveis de resposta das emissões otoacústicas por estímulo transiente em lactentes. Métodos Foi realizado, para comparação, o registro das emissões otoacústicas transientes em 154 neonatos: 54 bebês que sofreram asfixia perinatal, medida pela escala de Apgar e diagnóstico médico ao nascimento, e 100 bebês sem risco. Escores abaixo de 4 no primeiro minuto e/ou menores que 6 no quinto minuto foram considerados “Apgar baixo”. A análise estatística do conjunto de dados foi efetuada utilizando-se os testes não paramétricos de Kruskal, Wilcoxon e Mann-Whitney. Resultados Foram observados menores níveis de resposta nas emissões otoacústicas transientes para o grupo que sofreu asfixia perinatal, com valores estatisticamente significantes para as frequências de 2000, 3000 e 4000Hz na orelha direita e 2000 e 4000Hz na orelha esquerda. Conclusão A análise das características intrínsecas do exame de emissões otoacústicas transientes mostrou baixo desempenho das células ciliadas externas em neonatos que tiveram asfixia perinatal, o que pode afetar o desenvolvimento das habilidades auditivas nessa população.
Assessment of levels of otoacoustic emission response in neonates with perinatal asphyxia
Keywords: Asfixia neonatal; Índice de Apgar; Triagem neonatal; Asphyxia neonatorum; Apgar score; Neonatal screening